2012
DOI: 10.3390/su4112785
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of Small-Scale Fisheries in Elmina, Ghana

Abstract: Abstract:In order to achieve sustainable fishing livelihoods in coastal communities, data on profitability of small-scale fisheries relative to fish species hauled and gear types used by fishermen is required as part of a broader fisheries management strategy. This study was undertaken with this in mind. Interviews were conducted among 60 fishermen between February and March 2010. Economic assessment of small-scale fishing activities were done using questionnaires based on direct market pricing and contingent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
(1 reference statement)
1
19
0
2
Order By: Relevance
“…D. angolensis is widely distributed in the Eastern Central Atlantic along the West Coast of Africa from Morocco to Angola, including Canary Islands (Rico et al 1995). The economic value of D. angolensis is driving overfishing in some regions, with substantial (10%/year) population decline (Aheto et al 2012). Thus, the species is now classified as 'Near Threatened' in the Red List of Threatened Species (Pollard et al 2014).…”
mentioning
confidence: 99%
“…D. angolensis is widely distributed in the Eastern Central Atlantic along the West Coast of Africa from Morocco to Angola, including Canary Islands (Rico et al 1995). The economic value of D. angolensis is driving overfishing in some regions, with substantial (10%/year) population decline (Aheto et al 2012). Thus, the species is now classified as 'Near Threatened' in the Red List of Threatened Species (Pollard et al 2014).…”
mentioning
confidence: 99%
“…This study was conducted from February 2016 to June 2018 in Elmina (5°5 0 N 1°21 0 W) ( Fig. 1a & b) which is the third largest sh landing site in Ghana (Aheto et al, 2012). Elmina was purposively selected because it contributes about 15% of the country's total sh output (Hen Mpoano, 2015a) and has the highest intensity of saiko operations in the country (Hen Mpoano, 2015b).).…”
Section: Study Areamentioning
confidence: 99%
“…The dependency on fishing, however, makes it very difficult to implement effective strategies to prevent over-exploitation by fishermen and local communities and this has resulted in the decline of fish populations and other biota associated with seagrass. Other studies, too, have reported that small-scale fishing activities have had a negative impact on seagrass and other biota associated with seagrass in East Lombok (Satyawan et al, 2014), in reef flats and seagrass bed areas has reduced the population of the biota in the coastal waters (McCloskey and Unsworth, 2015) and high rates of exploitation mean that stocks generally cannot sustain expected levels of economic return (Aheto et al, 2012) and a relationship between the significant decline in catches in Indonesian waters and damage to seagrass beds . Furthermore, many of seagrass habitats damage caused to from community activities, commercial fishing and aquaculture (Brigitta et al, 2014).…”
Section: Threats To the Sustainability Of The Ecological Functions Ofmentioning
confidence: 99%